A Beyoncé Feminist - Keleta-Mae, Naila (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
Beyoncé’s album Beyoncé is a vexing articulation of twenty-first century mainstream feminism that captivated audiences worldwide. Whether or not feminist scholars, activists, or artists agree with Beyoncé’s discourse, her influence on popular culture is undeniable and it would be negligent for those of us invested in women’s and gender studies to dismiss the album or its principal artist.